ANALISIS DAMPAK KELUARGA TERHADAP KESULITAN BELAJAR SISWA PADA MATA PEMBELAJARAN KEWARGANEGARAAN DI MAN 1 MEDAN - Nora Adi Anna Harahap (STKIP Subang, 2022)
The purpose of this study was to see the effect of the family environment on students' learning Citizenship difficulties in each subject of MAN 1 Medan. The subjects of this study were several students, totaling 100 students, while the subjects of this study were the influence of the family environment on students' learning difficulties in the subjects of MAN 1 Medan. Data collection techniques used by the author are questionnaires and documentation. Data analysis was performed using a quantitative approach with linear regression analysis. Based on the research results, it is known that the family environment influences the learning difficulties of students in financial subjects at Madrasah Aliyah Medan City. Based on the calculation results, it is obtained that the coefficient of R squared = 0.533 = 53.3%, meaning that the family environment variable affects the student's learning difficulty variable by 53.3%, the remaining 46.7% is accounted for by other variables. which have . not included. in this research.